Adverse childhood experiences (ACEs), psychotropic medication prescription, and continued offending among youth with serious offending histories in juvenile justice residential placement. (November 2022) - Wolff, Kevin T.; Baglivio, Michael T.; Intravia, Jonathan
Abstract: Purpose: Adverse childhood experiences (ACEs) are linked to a multitude of deleterious outcomes including, but not limited to, persistent mental and physical health problems, increased justice system involvement, and chronic delinquency. Using a statewide multiyear sample of youth completing long-term juvenile justice residential placement, this study extends prior work by assessing the association between childhood aversity, the prescription of psychotropic medication, and continued delinquency. We additionally explore whether these associations vary across race/ethnicity and sex. Methods: Binary logistic regression and structural equation modeling are used to assess the relationship of cumulative ACEs with psychotropic medication prescription. Logistic regression models are used to assess which covariates, including cumulative ACEs and psychotropic medication, are associated with continued offending. Lastly, we examine the moderating effect of race/ethnicity and sex on the association between the prescription of psychotropic medication and continued delinquency. Results: ACE exposure increases mental health indicators, which then increase the likelihood of psychotropic medication prescription. ACEs increase reoffending; however, psychotropic medication prescription is unrelated to recidivism. The ACE effect and non-significance of psychotropic medication on recidivism was consistent across sex and race/ethnicity. Conclusion: ACEs are related to both psychotropic medication prescription during placement and subsequent recidivism, yielding juvenile justice policy implications. Highlights: Male, Black, Hispanic youth are less likely to be prescribed psychotropic medication. ACEs are associated with an in increase psychotropic medication prescription. ACEs contribute indirectly to psychotropic medication prescription. Heightened ACEs increase recidivism odds, psychotropic medication does not. Results are consistent across sex and race/ethnicity.